Answers

2015-02-19T21:00:06+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Cotθcosθ = cscθ - sinθ
(cosθ/sinθ)cosθ = cscθ - sinθ
[(cosθ)^2]/sinθ = cscθ - sinθ
[1-(sinθ)^2]/sinθ = cscθ - sinθ
1/sinθ - sinθ = cscθ - sinθ
cscθ - sinθ = cscθ - sinθ





0
2015-02-20T19:24:32+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let x=theta(I don't have the theta symbol)

cotxcosx=cscx-sinx
since cot is \frac{cosx}{sinx}
\frac{cosx}{sinx}(cosx)=cscx-sinx
\frac{cos^2x}{sinx}=cscx-sinx
since cos²x=1-sin²x
Substitute
\frac{1-sin^2x}{sinx}=cscx-sinx
Separate the 1-sin²x
\frac{1}{sinx}-\frac{sin^2x}{sinx}=cscx-sinx
\frac{1}{sinx}=cscx;
cscx-sinx=cscx-sinx

Hope this helps =)

0